2001
DOI: 10.1254/jjp.87.117
|View full text |Cite
|
Sign up to set email alerts
|

Lowered Susceptibility of Muscarinic Receptor Involved in Salivary Secretion of Streptozotocin-Induced Diabetic Rats

Abstract: ABSTRACT-We investigated the responses of salivary secretion and the susceptibility of the muscarinic receptors in the salivary glands of the streptozotocin (STZ)-induced diabetic rats (STZ rats). Giving water ad libitum, the amount of whole saliva with no stimulation was similar in the STZ and the control rats. Pilocarpine increased salivary secretion in both groups, although the effect in the STZ rats was two to three fold less than in the control rats. If the animals were restricted from taking water for 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
2
28
1
3
Order By: Relevance
“…Differences in the tissue responses between parotid and submandibular glands have already been reported for chemically induced diabetic rats, mainly in terms of parotid gland weight, which did not show significant alterations (Anderson and Johnson, 1981). Also, chemically induced diabetic rats submitted to glycemic control for a period of 1 hr to 7 days demonstrated recovery of salivary secretion levels and a decline in the accumulation of lipid droplets in the cytoplasm of parotid and submandibular salivary glands (Anderson, 1983;Morris et al, 1992;Watanabe et al, 2001). However, the authors emphasized that this treatment does not reflect total recovery of glandular function or morphology.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Differences in the tissue responses between parotid and submandibular glands have already been reported for chemically induced diabetic rats, mainly in terms of parotid gland weight, which did not show significant alterations (Anderson and Johnson, 1981). Also, chemically induced diabetic rats submitted to glycemic control for a period of 1 hr to 7 days demonstrated recovery of salivary secretion levels and a decline in the accumulation of lipid droplets in the cytoplasm of parotid and submandibular salivary glands (Anderson, 1983;Morris et al, 1992;Watanabe et al, 2001). However, the authors emphasized that this treatment does not reflect total recovery of glandular function or morphology.…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, an increase in protein synthesis in the submandibular glands has been observed in chemically induced diabetic rats after they had received a single dose of insulin. However, the authors did not characterize both functional and morphological recovery of the glands (Anderson and Shapiro, 1980;Watanabe et al, 2001). Also, no significant recovery of parotid gland weight was observed in other studies administering a single dose of insulin to chemically induced diabetic rats (Anderson, 1987;Pinkstaff, 1996).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Saliva was collected as described previous ly (Watanabe et al, 2001). Briefly, the mice, anesthetized with pentobarbital sodium (50 mg/kg i.p), were secured in a supine position, and a tracheal tube was inserted to support respiration.…”
Section: Collection Of Saliva From Parotid and Submandibular/sublingumentioning
confidence: 99%
“…The transcripts for BMP7 are mediated via its specific receptor, ALK2, and non-specific receptor, ALK3 (Maric et al, 2003). 4 An earlier study demonstrated that the submandibular gland was more strongly resistant to diabetic stress than the other salivary gland s (Watanabe et al, 2001). These results suggested differences in sensibility, producibility, or expression of BMP7 in salivary gland.…”
Section: Introductionmentioning
confidence: 99%